Immunometabolism at the crossroads of obesity and cancer—a Keystone Symposia report - Cable, Jennifer; Rathmell, Jeffrey C.; Pearce, Erika L.; Ho, Ping‐Chih; Haigis, Marcia C.; Mamedov, Murad R.; Wu, Meng‐Ju; Kaech, Susan M.; Lynch, Lydia; Febbraio, Mark A.; Bapat, Sagar P.; Hong, Hanna S.; et al. (Annals of the New York Academy of Sciences, 2023)
Immunometabolism considers the relationship between metabolism and immunity. Typically, researchers focus on either the metabolic pathways within immune cells that affect their function or the impact of immune cells on systemic metabolism. A more holistic approach that considers both these viewpoints is needed. On September 5–8, 2022, experts in the field of immunometabolism met for the Keystone symposium “Immunometabolism at the Crossroads of Obesity and Cancer” to present recent research across the field of immunometabolism, with the setting of obesity and cancer as an ideal example of the complex interplay between metabolism, immunity, and cancer. Speakers highlighted new insights on the metabolic links between tumor cells and immune cells, with a focus on leveraging unique metabolic vulnerabilities of different cell types in the tumor microenvironment as therapeutic targets and demonstrated the effects of diet, the microbiome, and obesity on immune system function and cancer pathogenesis and therapy. Finally, speakers presented new technologies to interrogate the immune system and uncover novel metabolic pathways important for immunity. Immunometabolism considers the relationship between metabolism and immunity. Typically, researchers focus on either the metabolic pathways within immune cells that affect their function or the impact of immune cells on systemic metabolism. This report presents recent research across the field of immunometabolism, with the setting of obesity and cancer as an ideal example of the complex interplay between metabolism, immunity, and cancer.